2022
DOI: 10.1186/s13072-022-00461-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analyses of MEN1 missense mutations identify disruption of menin–MLL and menin–JunD interactions as critical requirements for molecular pathogenicity

Abstract: Background Loss-of-function mutations of the multiple endocrine neoplasia type 1 (MEN1) gene are causal to the MEN1 tumor syndrome, but they are also commonly found in sporadic pancreatic neuroendocrine tumors and other types of cancers. The MEN1 gene product, menin, is involved in transcriptional and chromatin regulation, most prominently as an integral component of KMT2A/MLL1 and KMT2B/MLL2 containing COMPASS-like histone H3K4 methyltransferase complexes. In a mutually exclusive fashion, meni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 65 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…Prior studies focused on mapping structural defects at the protein level have shown that mutations arising in specific functional domains of menin can impair protein-protein interactions that may result in altered gene expression leading to cell proliferation, altered cell-specification, and NET development [24,[39][40][41][42] . For instance, a recent in silico analysis of 253 disease related MEN1 missense mutations identified three single nucleotide variants that impaired the binding affinity of menin with the Mixed Lineage Leukemia 1 (MLL) protein [42] . In contrast, these mutations did not have an apparent effect on the menin-JUND interaction, further raising the potential for context-specific regulation that might dictate the tumor suppressive and oncogenic properties of menin.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies focused on mapping structural defects at the protein level have shown that mutations arising in specific functional domains of menin can impair protein-protein interactions that may result in altered gene expression leading to cell proliferation, altered cell-specification, and NET development [24,[39][40][41][42] . For instance, a recent in silico analysis of 253 disease related MEN1 missense mutations identified three single nucleotide variants that impaired the binding affinity of menin with the Mixed Lineage Leukemia 1 (MLL) protein [42] . In contrast, these mutations did not have an apparent effect on the menin-JUND interaction, further raising the potential for context-specific regulation that might dictate the tumor suppressive and oncogenic properties of menin.…”
Section: Discussionmentioning
confidence: 99%
“…MENIN acts as a tumor suppressor in NENs; 11 however, its exact mechanism of action is unclear. In contrast, MENIN functions as a co‐oncogene in some hematopoietic malignancies by directing a mutated lysine methyl transferase KMT2A/MLL protein to genes controlling cell proliferation 32,33 …”
Section: Men1 Mutations In Gastrinomasmentioning
confidence: 99%
“…Missense mutations have been identified throughout the whole coding domain, yet no hotspots or clear genotype–phenotype correlations have been predictably identified 38,40,41,42 . Despite this, the majority of MEN1 ‐associated missense mutations yield aberrantly functioning proteins that are unstable and exhibit reduced or absent nuclear MENIN levels compared to the wild‐type protein 32,43,44 . Nevertheless, more research is necessary to establish whether residual MENIN in tumors display a wild type or mutated genotype and phenotype.…”
Section: Men1 Mutations In Gastrinomasmentioning
confidence: 99%
See 2 more Smart Citations